Herbicide resistance in Rumex dentatus A threat to sustainable wheat production in north-western India - Dhanda, Sachin; Kaur, Simerjeet; Chaudhary, Ankur (Indian Farming, 2022)
Herbicide resistance in weeds is becoming a major challenge in Indian agriculture which is an alarming signal for sustainable crop production. Earlier herbicide resistance was confined t o Phalaris minor only in wheat crop but now there are some reports of resistance in Rumex dentatus to metsulfuron methyl in Haryana and Punjab. To confirm this, a study was conducted at Punjab Agricultural University, Ludhiana during 2018-19 and 2019-20. This study showed that resistance has evolved in Rumex dentatus against metsulfuron methyl in many rice-wheat growing regions of Haryana and Punjab. This first report of resistance from Punjab indicates the spread of resistance in R. dentatus. Therefore, an integrated approach is required to control this resistance problem in R. dentatus.